Assessment of Noise Levels of Churches in the Kpone Katamanso Municipal Assembly in Ghana - Lyndon N. A. Sackey; Joel Abugre; Bernard Fei-Baffoe; Ebenezer Y. E. Amuah; Richmond Yeboah Amoako (The Scientific World Journal)
Different sound levels are encountered by pastors, ministers, and the whole congregation during church services, which may extend for hours, and also by people living close to these churches. This can have an adverse effect on their health. The maximum allowable noise level in worship places is 65 dB (A), according to the Ghana Standards Authority (GSA). The aim of the study was to quantify the noise pollution levels of the churches in Kpone Katamanso Municipal Assembly (KKMA) and assess the equivalent noise levels of the churches’ indoor and outdoor spaces. This investigation is being conducted due to the high number of churches and the noise emanating from these churches in the Kpone Katamanso Municipality and the possible impact on human health. Thirty churches were chosen at random for the study; on Sundays between the hours of 7.30 and 12.0 pm, sound levels in churches were measured using a portable General Class 1 Meter type DSM403SD with a data logging system. MS Excel was used to evaluate the data and determine characteristics including noise exposure levels (NEL), background noise level (L90), severe noise level (L10), and equivalent noise level (Leq). The indoor equivalent noise level ranges from 74.5 dB (A) to 104.1 dB (A), and the outdoor equivalent noise level ranges from 52.6 dB (A) to 85.3 dB (A). All of the noise levels found indoors of the churches were greater than the 65 dB (A) safe allowable limit, putting the congregants and residents at risk for a variety of physiological and psychological problems.